Finance and Economic Development - Ugo Panizza (Revue Internationale de Politique de Développement)
Published by Palgrave MacmillanThis chapter reviews the literature on finance and economic development. It starts with a description of the roles of finance, a definition of financial efficiency, and a discussion of whether countries may have financial sectors that are ‘too large’ compared to the size of the domestic economy. Next, the author describes several indicators of financial development and reviews the literature on the relationship between financial development and economic growth. In the literature review, he discusses in detail some recent evidence indicating that the marginal contribution of financial development to gross domestic product (GDP) growth becomes negative when credit to the private sector reaches 110 per cent of GDP. The chapter concludes with some policy conclusions targeted to developing countries.